The Implementation of Task-Based Language Teaching to Develop Students’ Grammar Accuracy - Soali, Muhammad; Ashadi , Ashadi; Hepriansyah, Azwan (Green Publisher Indonesia, 2023)
This research aims to find out; (1) whether task-based language teaching can develop students’ grammar accuracy; and (2) whether the implementation of Task-Based Language Teaching can develop class condition in grammar class of the second-grade students of English Department of Universitas Harapan Bangsa. The method used in this research is classroom action research. It was conducted in two cycles from October to December 2021 at the first-grade students of English Department of Universitas Harapan Bangsa. The research result shows that the use of Task-Based Language Teaching can develop the students’ grammar accuracy. The students succeed to make sentences in various tenses with correct form and meaning. The results of all cycles conducted as follows; the average score of post-tests in cycle I is 64, and post-test in cycle II is 73. The class condition also became better since the method was applied. They are more active joining the learning process. They applied the language rules they learned communicatively in the spoken and written forms. This condition made them aware of their ability to use the standard language in the communication. In conclusion, task-based language instruction can improve the classroom environment and the students' grammar proficiency. Both the academic performance and the learning environment of the students are benefited by this approach.